Comparative Methods of Increasing Drug Dissolution Rate - Rizqi, Syifa Maulidia; Chabib, Lutfi (Jurnal Farmasi Udayana; Vol. 12, No. 2, tahun 2023, 2024)
The speed of dissolution becomes an important part in the manufacture of drugs, because it is related to drug absorption and bioavailability. In order to achieve a good dissolution rate, various methods with certain criteria are needed. This review article aims to find out various methods that can be used to increase the speed of drug dissolution, and can be used as a reference for choosing the most appropriate dissolution method. The article review method used is a narrative review type in the form of a description or explanation of methods for increasing dissolution as a comparison in terms of method selection. Journals were obtained through chrome, google scholar and researchgate using 16 journals. The results obtained are that there are several methods that can increase dissolution including amorphous co, the use of surfactants and so on. The conclusion obtained from this review of the article is that there are various methods of increasing dissolution such as the use of surfactants, co-crystals, amorphous cos and so on. Keywords: dissolution; method; narrative review